Emotional Intelligence and Teachers’ Entrepreneurial Behavior: A Gender-Based Analaysis in Surakarta - Ambar Nabila Setianingrum; Susilaningsih Susilaningsih; Muhammad Sabandi (Jurnal Paedagogy, 2026)
This study aims to analyze the influence of emotional intelligence on teachers’ entrepreneurial behavior, with gender included as a moderating variable. A quantitative survey design was employed, involving a sample of 102 teachers from SMK Negeri 1 Surakarta and SMK Negeri 6 Surakarta. Data were collected using a closed-ended questionnaire, and the analysis was conducted using hierarchical regression modeling. The results indicate that emotional intelligence has a significant and positive effect on teachers’ entrepreneurial behavior, with a coefficient of determination (R²) of 0.772. However, gender does not moderate the relationship between emotional intelligence and teachers’ entrepreneurial behavior. These findings suggest that the development of teachers’ emotional intelligence plays a crucial role in fostering entrepreneurial behavior, regardless of gender differences. Accordingly, this study recommends that school principals provide emotional intelligence development programs, such as emotional regulation and emotion management training, as well as implement balanced work policies to reduce occupational pressure. Such initiatives can support teachers’ emotional well-being and optimize the expression of entrepreneurial behavior among both male and female teachers.